Dry land arboriculture - Pelham, Jesse Leroy (My University, 1907)
Introduction: The growing of trees without irrigation in regions having a limited rain fall is known as arid or dry-land arboriculture. In such regions, where dry farming is practiced, the annual rain fall ranges from eight to twenty-eight inches. Government records give the average rainfall for western Kansas for the last ten years as 19.78 inches, and classifies the climate as subhumid or semiarid. The chief characteristics are those common throughout the Great Plains. As a rule the average precipitation is sufficient for paying crops. The summer rains come mostly from local thunder storms, whose course may or may not overlap. As a result of which one locality often receives sufficient rain during a season, while another but a few miles distant will suffer from drouth. The average annual rainfall at Hays, Kansas is 20.9 inches, while that at Wallace, due west of Hays and nearer the Colorado line, is but 16.1 inches, For the last thirty-five years a Weather Bureau record has been kept at Dodge, Kansas, and during that period the precipitation of the driest year was 10.1 inches, while the wettest year had 33.7 inches. This gives an average precipitationat Dodge of about 20 inches, and this if well distributed is sufficient for the growth of many tree species. This same fluctuation as shown by the Dodge records, prevails throughout the plain region of western Nebraska, Kansas, eastern Colorado, the Territory and northern Texas. While the greater part of the rainfall comes at the time of greatest need, it also comes at the time of the greatest evaporation, Between April 1st and October 1st. High winds increase the evaporation. Government records and experiments show…
Citation: Pelham, Jesse Leroy. Dry land arboriculture. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Arboriculture; Tree Growing; Conditions for Tree Growing; Techniques of Arboriculture; Theses